Appraisal of Muslim Women’s Status in Tehmina Durrani's My Feudal Lord (Patan Pragya, 2025)
This paper scrutinizes the impact of Islamic laws and the broader process of Islamization on women’s lives as represented in TehminaDurrani’s memoir My Feudal Lord.The female characters are so dominated in socio-cultural contexts of Pakistan that primarily practices Islam as the main guiding principle to affect the social practices and behaviors. Because of the rules led predominantly by patriarchy, women often suffer marginalization and oppression in both personal and public lives as portrayed in the novel. The objective of the paper is to critical analyze the impact of Islam on socio-cultural lives of women in Pakistan as fictionalized by Tehmina—a feminist writer and an advocate of human rights—who observes women rights as human rights in a broader context. By reading the literary text closely, it is analyzed from the feminist perspective. The combination of historical and legal context, the impact of Islam is explored. The researcher argues that Durrani’s narrative not only exposes personal abuse within a feudal marriage but also illuminates how legal frameworks and socio-religious norms—especially those reinforced under Pakistan’s Islamization policies—constrained women’s agency, legitimized male authority, and complicated access to justice. How women are subjugated in a societal framework in Pakistani society holds significance. The article concludes that Durrani’s depiction functions as both a personal testimony and a critique of institutional structures that subordinate females and it suggests avenues through which legal reform and feminist activism have sought to mitigate these harms. This paper has employed the qualitative research design to underscore the effect of Islam on lives of female characters in South Asian context in general and in Pakistani Muslim society in particular.